Figurativeness and Humour in Covid-19-Related Internet Memes - Cighir, Anca Irina (International Journal of Language and Literary Studies, 2024)
When social dilemmas arise, people often turn to humour and pop culture to find answers. At the beginning of the COVID-19 pandemic social networks flooded with internet memes. Internet memes are “a kind of modern folklore in which values are constructed through photoshopped images” (Shifman, 2014, p.14) and they often use figurative devices, being a genre of humour and creativity. The examination of internet memes can provide a way of understanding how people managed to cope with one of the most challenging crises of our times. This paper aims to analyse a series of COVID-19-related memes in order to show how the collectively lived experience of COVID-19 pandemic has been processed and perceived by social media users. To this end we collected and analysed internet memes created in 2020 with the aid of cinematography and whose captions are written in English. We also investigated factors that shaped people’s understandings of the memes. Our research focused on the analysis of the CONTAINER metaphor and orientational metaphors and also investigated the cognitive base of humour, that is, the incongruity “or incompatibility or contrast inside or between conceptual frames of knowledge – either figurative or literal” (Kovecses, 2015, p.135). In the current study we used both qualitative and quantitative methods which helped us interpret people’s perception of the metaphorical usage embedded in the Internet memes used in our research. Our findings lead us to conclude that in most interpretations of the memes the visual mode had a greater impact on the receivers and led them to a correct interpretation of the metaphors embedded.